Litter quality outweighs climate in driving grassland root decomposition - Yang, Jingjing; Yang, Zhanbo; Zhang, Runzhi; Guan, Pingting; Xu, Taihai; Tang, Yao; Ren, Guoling (Frontiers in Plant Science, 2025)
IntroductionRoot decomposition plays a critical role in nutrient cycling and carbon storage in grassland ecosystems, yet its global drivers remain poorly understood.MethodsThe study synthesized global data on root decomposition in grasslands to assess the relative importance of climate and litter quality, and to quantify the effects of environmental and biotic factors using a comprehensive meta-analysis.ResultsResults indicated that, at the global scale, litter quality exerted a stronger influence on root decomposition than climatic variables. Random forest analysis identified the ratio of acid-unhydrolyzable residue to nitrogen (AUR:N) and AUR as the most important predictors of mass loss, both of which were significantly and negatively correlated with mass loss. The meta-analysis further demonstrated that both environmental and biotic factors significantly affected root decomposition. Among environmental factors, nitrogen addition (+4.49%), phosphorus addition (+16.26%), warming (+9.80%), increased precipitation (+5.95%), and elevated CO2 (+14.03%) were found to promote root decomposition, while reduced precipitation (−15.60%) had the negative effect. With respect to biotic factors, grazing (+7.51%) significantly increased decomposition, whereas vegetated soil (−27.84%), increased plant species richness (−4.99%), increased root litter richness (−5.93%), home-field decomposition (−4.34%), and soil biota exclusion (−10.40%) decreased it.DiscussionThese findings highlight the dominant role of litter quality over climate in regulating root decomposition at a global scale, and underscore the sensitivity of belowground processes to environmental and biotic disturbances in grassland ecosystems.